(untitled) (International Journal of Food and Nutritional Sciences, 2021)
According to International Labor Organization, rainfall plays a very important role in the overall development of a country like India where the agriculture workforce includes more than 50% of the population, of which 80% is from rural India. Thus, it is necessary to understand the rainfall pattern and to revise it periodically to understand the changes in it, so that necessary changes can be done on agricultural models and to mitigate agricultural hazards from pre-monsoon and returning monsoon. This paper is an evaluation of pre-monsoon and returning monsoon rainfall patterns for three districts in the state of Maharashtra in India which are adjoin to the Western Ghats which are known as Sahyadri. Variation in rainfall can be clearly observed through these districts belonging to the same natural division.